As rochas vulcânicas da Ilha São Jorge, Açores (Portugal) : petrografia e geoquímica - Mecenas, Karoline Ferreira da Silva (Pós-Graduação em Geociências e Análise de Bacias, 2019)
São Jorge Island is part of Central Group from Azores Archipelago (Portugal), which is located near the triple junction among North American, Euro-Asian and African lithospheric plates, in the North Atlantic region. The volcanism in that island is fissural type, with the preferential orientation WNW-ESE, which reveals the importance of the tectonic control during the volcanic activity. The studied magmatism is influenced by the interaction between the Hotspot of the Azores and the Meso-Atlantic Ridge. The island volcanostratigraphy is composed of three volcanic complexes named Topo (East of the island), Rosais (West of the island) and Manadas (center of the island). According to Ribeiro (2011), the oldest geochronological age reported for São Jorge Island is 1.3 ± 0.0035 Ma (40Ar / 39Ar). Based on petrographic data, the rocks of the island show medium to fine granulometry, porphyritic, microporphyritic, glomeroporphyritic, intergranular, pilotaxytic, trachytic and intersertal textures. According to geochemical data, rocks are classified as basanites (4.9-12.2% olivine, 4.6-23.2% augite, 5.4-8.3% plagioclase, 0-0.3% opaque minerals and 59.2-81.9% matrix), alkaline basalts (0.6-3.3% olivine, 0-3.5% augite, 6.3-17.5% plagioclase, 0-1, 2% kaersutite, 0-1.8% opaque minerals and 79.2-88.2% matrix) and hawaiites (0-5.6% olivine, 0-3.2% augite, 0- 22.2% plagioclase, 0-1.1% kaersutite, 0-1.6% opaque minerals and 69-99.7% matrix). The matrix presents mineralogical composition like phenocrysts composition (olivine, augite, plagioclase, kaersutite and opaque minerals), as well as volcanic glass and rounded-elongated vesicles. Reabsorption textures, sheathing, reaction edges and zonation are common features in the phenocrysts of the studied rocks. These features indicate that the magma underwent rapid decompression, with sudden variation of temperature and pressure. The trace element patterns show enrichment in LILE and HFSE relative to the ETRP. The ETR patterns present ETRL enrichment compared to ETRP, with Eu negative ...